Cerebral amyloid angiopathy in posttransplant patients with hereditary ATTR amyloidosis. (23rd August 2016) - Sekijima, Yoshiki; Yazaki, Masahide; Oguchi, Kazuhiro; Ezawa, Naoki; Yoshinaga, Tsuneaki; Yamada, Mitsunori; Yahikozawa, Hiroyuki; Watanabe, Masahide; Kametani, Fuyuki; Ikeda, Shu-ichi
Abstract : Objective: To investigate the prevalence and clinical features of posttransplant CNS symptoms in patients with hereditary ATTR amyloidosis and their Pittsburgh compound B (PiB)–PET imaging correlates. Methods: We monitored prevalence and type of CNS symptoms in 53 consecutive posttransplant patients with hereditary ATTR amyloidosis. 11 C-PiB-PET was performed in 15 patients with various disease durations. We also analyzed pathologic and biochemical characteristics of ATTR amyloid deposition in the brain of a posttransplant patient. Results: Transient focal neurologic episodes (TFNEs) attributed to ATTR-type cerebral amyloid angiopathy (CAA) were found in 11.3% of posttransplant hereditary ATTR amyloidosis patients. TFNE occurred on average 16.8 years after onset of the disease. Patients with longer duration of illness (≥10 years) showed increased 11 C-PiB retention in the brain. The 11 C-PiB accumulation pattern in hereditary ATTR amyloidosis was unique and different from those in Alzheimer disease or Aβ-type CAA. In the autopsy case, ATTR amyloid deposition was mainly localized to leptomeningeal vessels and leptomeninges of the brain. Amyloid fibrils in the brain were almost completely composed of variant transthyretin (TTR). Conclusions: TFNE due to ATTR-type CAA occurred frequently in posttransplant patients with long disease durations. 11 C-PiB-PET is a useful diagnostic tool for ATTR-type CAA. ATTR amyloid deposition in the CNS, as measured by PiB-PET, was detected approximately 10 years before onset of TFNE.